Dr. Clare R. Baltazar a portrait of an entomologist par excellence - Corpuz-Raros, L.A. (Philippines Rushing Water Publishers, 1995)
"The Staff and Alumni Department of Entomology College of Agriculture UP Los Banos present this testimonial plaque to Dr. Clare R. Baltazar, University Professor, in recognition of her outstanding contribution as a teacher, scientist and administrator in the field of Entomology. Dr. Baltazar is the epitomy of extraordinary intellect, dedication humility and wholesome humor. Her display of brilliance in the classroom is attested to by her students through the years, at the superior quality of her scientific work in systematics and biological control, by her peers. The years spent in the subject of her interest and pioneering work, the taxonomy of Philippine Hymenoptera yielded many published articles and books which are now living monuments of her lifetime career in science. Her catalogues of Philippine insects covered several orders, a manifestation of her mastery of Entomology which now serve as an inspiring legacy to guide future generations of Filipino entomologists. Dr. Baltazar is a distinct class of her own and has established the standard of excellence for all Filipino entomologists to emulate. As administrator her uncanny way of harmonizing the diverse temperaments of entomologists brought forth the flowering of creativity in the department."
Keywords: Baltazar, Clare R. -- Entomologist; Insects -- Philippines